In Search of the Missing Links Between Economic Insecurity and Political Protest: Why Does Neoliberalism Evoke Identity Politics Instead of Class Interests? - Siltala, Juha (Frontiers in Sociology, 2020)
The prospect of the social backsliding of middle-class groups in western countries has not benefited the left but fueled right-wing populism. This article examines mediating and moderating factors between economic threat and political choices. The shift of liberals toward conservatism and the activation of passive authoritarians explain sudden changes more than dispositional factors. Attachment to groups under stress activates coalitional mindsets, and coalitional competition for scarce resources matches the conservative propensity to detect threats from outgroups. Risk-averse right-wing authoritarians should recoil from social-dominance oriented risk-takers but they follow winners despite their mutual differences concerning family values. Authoritarian aggression unites RWA and SDO, but politically passive right-wing authoritarians can also follow their economic interests, when these are not entangled with cultural values. Right-wing populists have been able to compensate economic insecurity with epistemic security. Identity politics supports the coherence of right-wing populist parties but divides leftist/liberal groups due to intersectional competition for victimhood.